Observations on status and trends of agricultural extension and inequality in Uganda - Samuel, T. Ledermann; Jock, R. Anderson; Carl, E. Pray (World Development Sustainability, 2024)
The global pandemic has accentuated inequalities, with vulnerable populations in developing countries fairing worst. In rural sub-Saharan Africa, restrictions on mobility to limit the spread of COVID-19 negatively impacted access to extension services and inputs by farmers. In response, countries deployed digital technologies to meet some of these challenges in the context of existing income, gender and spatial inequalities and historic declines in funding for public extension. Focusing on Uganda, which had one of the longest and strictest lockdowns, the paper used panel datasets of farmers from 2005 to 2019/2020 and found persistent socio-economic and gender inequalities in access to extension. Data from rapid rural surveys from 2020 to 2021 and a review of recent literature suggest these inequalities increased during the pandemic. The paper then builds on the structure and reforms of the current extension system to assess the potential of the digital services and their added value given the inequalities observed. The paper finds that the ability of government-led, inclusive, digital extension services is limited unless investments in extension are increased. In light of long-term declines in funding for extension, future research should focus on the effectiveness of policies to encourage private sector-led digital extension efforts to strengthen the pro-poor nature of agricultural growth.